Neurocognitive and mental health outcomes in children with tungiasis: a cross-sectional study in rural Kenya and Uganda - Otieno, Berrick; Elson, Lynne; Matharu, Abneel K.; Riithi, Naomi; Chongwo, Esther; Katana, Khamis; Nasambu, Carophine; Mutebi, Francis; Feldmeier, Herman; Krücken, Jürgen; Fillinger, Ulrike; Abubakar, Amina (BioMed Central, 2023)
Abstract Background Tungiasis, a neglected tropical parasitosis, disproportionately afects children. Few empirical studies have reported neurocognitive and mental health outcomes of children with ectoparasitic skin diseases like tungiasis. Pathophysiology of tungiasis suggests it could detrimentally afect cognition and behaviour. This study pioneered the investigation of neurocognitive and mental health outcomes in children with tungiasis. Methods This was a multi-site cross-sectional study including 454 quasi-randomly sampled school-children aged 8–14 from 48 randomly selected schools in two counties in Kenya and a district in Uganda. The participants were stratifed into infected and uninfected based on the presence of tungiasis. The infected were further classifed into mild and severe infection groups based on the intensity of the infection. Adapted, validated, and standardized measures of cognition and mental health such as Raven Matrices and Child Behaviour Checklist were used to collect data. Statistical tests including a multilevel, generalized mixed-efects linear models with family link set to identity were used to compare the scores of uninfected and infected children and to identify other potential risk factors for neurocognitive and behavioural outcomes. Results When adjusted for covariates, mild infection was associated with lower scores in literacy [adjusted β(aβ)=− 8.9; 95% confdence interval (CI) − 17.2, − 0.6], language (aβ=− 1.7; 95% CI − 3.2, − 0.3), cognitive fexibility (aβ=− 6.1; 95% CI − 10.4, − 1.7) and working memory (aβ=− 0.3; 95% CI − 0.6, − 0.1). Severe infection was associated with lower scores in literacy (aβ=− 11.0; 95% CI − 19.3, − 2.8), response inhibition, (aβ=− 2.2; 95% CI − 4.2, − 0.2), fne motor control (aβ= − 0.7; 95% CI − 1.1, − 0.4) and numeracy (aβ=− 3; 95% CI − 5.5, − 0.4). Conclusions This study provides frst evidence that tungiasis is associated with poor neurocognitive functioning in children. Since tungiasis is a chronic disease with frequent reinfections, such negative efects may potentially impair their development and life achievements. Keywords Tungiasis, Tunga penetrans, Neglected tropical disease, Neurocognition, Mental health, School-aged children, Africa
Keywords: Tungiasis, Tunga penetrans, Neglected tropical disease, Neurocognition, Mental health, School-aged children, Africa